2015
DOI: 10.5772/60041
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resource Bundling on Third-Party Logistics Providers' Performance

Abstract: This research develops and tests a model of the effects of resources bundling on third-party logistics (3PL) providers' performance. Based on data from a survey of Malaysian 3PLs, basic and advanced technology and equipment resources, knowledge and relational resources, and demand management interfaces are identified. The bundling of advanced technology, knowledge resources, and demand management interface capability are found to enhance 3PLs' customer service innovation. Similar resource bundling (excluding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 53 publications
4
42
0
2
Order By: Relevance
“…In summary, previous research has suggested the strategic importance of relational resources through their critical impact on the firm's competitive advantages (Li and Ogunmokun, 2001;Story et al, 2009;Karia et al, 2015). This addresses the key role of the firm's relationships with its external partners, such as suppliers and customers (Karia et al, 2015).…”
Section: Relational Resourcesmentioning
confidence: 94%
See 2 more Smart Citations
“…In summary, previous research has suggested the strategic importance of relational resources through their critical impact on the firm's competitive advantages (Li and Ogunmokun, 2001;Story et al, 2009;Karia et al, 2015). This addresses the key role of the firm's relationships with its external partners, such as suppliers and customers (Karia et al, 2015).…”
Section: Relational Resourcesmentioning
confidence: 94%
“…Relational resources have been regarded as one of the critical resources for 3PL providers to achieve competitive advantages (Wong and Karia, 2010;Karia and Wong, 2013;Darkow et al, 2015). According to Karia et al (2015), relational resources refer to the strong relationships that the firm establishes with its suppliers and customers. Such resources are difficult and costly for the firm's rivals to imitate, because they require a long term to develop and involve significant ambiguity (Morgan and Hunt, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, it has strict requirements in information integrity, resource management, and product quality. 8,9 The cold chain monitoring and storage conditions are particularly important in maintaining designated environmental conditions, as stated in various international regulations, such as Hazard Analysis Critical Control Point, Good Agricultural Practice, and Food and Drug Administration. [10][11][12] It shows the importance of cargo traceability and monitoring, without which foodborne illnesses or quality deterioration may occur.…”
Section: Cold Chain Managementmentioning
confidence: 99%
“…Importance of quality management and its impact on the performance of businesses has been widely researched and plethora of literature is available on this topic (Ali, 2014;Czajkowska & Stasiak-Betlejewska, 2015;Fotopoulos & Psomas, 2010;Jaafreh & Al-abedallat, 2012;Nguyen, Phan & Matsui, 2018). Simultaneously many researchers, (Gavrea, Ilies & Stegerean, 2011;Karia & Wong, 2013;Karia, Wong, Asaari & Lai, 2015;Kraja & Osmani, 2015), have emphasized the importance of service competencies as a tool to get competitive advantage for better performance, but the direct impact of quality management practices on the integration capability of Logistics Service Providers (LSPs) is not duly researched. Gupta, Singh and Suri (2018) quoted a comprehensive definition as initially presented by Huo and Wei that logistics outsourcing is a long-term cooperation between a shipper and LSP for mutual benefit coming out of their mutual integration.…”
Section: Introductionmentioning
confidence: 99%